2020
DOI: 10.3390/jmse9010022
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Ocean Thermal Energy Conversion Resources in the East of Malaysia

Abstract: The Malaysian Government has set a target of achieving 20% penetration of Renewable Energy (RE) in the energy mix spectrum by 2025. In order to get closer to the target, Ocean Thermal Energy Conversion (OTEC) aligned with solar PV, biogas and biomass energy sources must be evaluated and comprehended. Hybrid OTEC systems consisting of energy and water production are currently under research and validation. Therefore, for the construction of a commercial OTEC plant, 1 MW or 2.5 MW, the choice of a strategic loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The researchers concluded that the maximum net power from Ge-OTEC is estimated to be 32.5 MW. In a study by Thirugnana et al, [74], the power generated by a hybrid OTEC system suggested for deployment in the Malaysian EEZ near Sabah's coast was estimated. The results conclude that the system can generate power equal to or four times higher than the Malaysian government's target set in 2025.…”
Section: Otec Resource In Malaysiamentioning
confidence: 99%
“…The researchers concluded that the maximum net power from Ge-OTEC is estimated to be 32.5 MW. In a study by Thirugnana et al, [74], the power generated by a hybrid OTEC system suggested for deployment in the Malaysian EEZ near Sabah's coast was estimated. The results conclude that the system can generate power equal to or four times higher than the Malaysian government's target set in 2025.…”
Section: Otec Resource In Malaysiamentioning
confidence: 99%
“…Working fluid Ammonia (NH3) [10] Gross turbine power 100-200 kW [15] Cold seawater 5 -8 °C [26] Seawater temperature difference at the condenser 5.8 °C [18] Warm seawater temperature 25.3-31.3 °C [27] Seawater temperature difference at the evaporator 3 °C [18] Refrigerant temperature at the evaporator outlet The numerical simulation was carried out in Matlab R2018a using the refrigerant's thermodynamic properties as obtained from CoolProp v6.1.3. At the evaporator's outlet, state 2 was used as the starting point for the calculation.…”
Section: Parameter Value Authormentioning
confidence: 99%
“…Apart from power generation, hybrid OTEC system, which is the latest and advanced OTEC technology, has the potential to be utilized for producing other side products such as desalinated water [2]. Furthermore, the deep seawater discharge used in an OTEC power plant could be exploited for the cultivation of blue economy for the benefits around island communities [3].This further highlights the OTEC's capabilities of fulfilling the United Nation (UN)'s Sustainable Development Goals (SDGs) such as goal 6 for Clean Water and Sanitation and goal 7 for Affordable and Clean Energy [4].…”
Section: Figure 1 Schematic Flow Diagram Of Hybrid Ocean Thermal Ener...mentioning
confidence: 99%